Mixed soft magnetic powder, method for preparing soft magnetic powder core from mixed soft magnetic powder, obtained product and application

By using A, B and C powder of different particle sizes and types, mixed soft magnetic powders, and using multiple steps to process, the problem of insufficient performance of existing metal magnetic powder cores is solved, and soft magnetic powder cores with high density, high magnetic permeability and low magnetic loss are prepared, meeting the high performance needs of electronic equipment.

CN119724806APending Publication Date: 2025-03-28SOLOMON (CHANGZHOU) ALLOY NEW MATERIAL CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411995722.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing metal magnetic powder cores have problems such as large loss, low saturated magnetic induction strength, low DC bias and high price, which cannot meet the needs of electronic equipment for high magnetic permeability, low loss and high DC bias capabilities.

Method used

Mixed soft magnetic powder, including A, B and C powder of different types and particle sizes, are prepared and screened by aerosolization, water atomization method or water atomization combined with water atomization method. The mixed soft magnetic powder after grading is annealed, passivated insulation, coated granulation, hot pressing molding and low temperature annealing to prepare a soft magnetic powder core with high density, high magnetic permeability and low magnetic loss.

Benefits of technology

It realizes high magnetic permeability (μ≥125), low magnetic loss (Pcv≤150mW/cm3) and high DC bias characteristics (≥76%), while reducing production costs and meeting the demand for high-performance magnetic powder cores of electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119724806A_ABST
    Figure CN119724806A_ABST
Patent Text Reader

Abstract

The invention discloses mixed soft magnetic powder, a method for preparing a soft magnetic powder core through the mixed soft magnetic powder, an obtained product and application. The mixed soft magnetic powder comprises powder A, powder B and powder C. The powder A and the powder B are independently at least one of iron-based amorphous alloy powder, iron-based nanocrystalline alloy powder and iron-based amorphous nanocrystalline alloy powder, the powder C is iron-based alloy powder, and the particle size of the powder A is larger than that of the powder C and larger than that of the powder B. The uniformly mixed soft magnetic powder is subjected to annealing treatment under the protection of hydrogen, then passivation insulation treatment and coating granulation treatment are performed, screening is performed, the screened powder is pressed, and the soft magnetic powder core with high density, high magnetic conductivity, low loss and good direct current bias capability can be obtained after annealing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of soft magnetic materials, and in particular to a mixed soft magnetic powder, a method for preparing a soft magnetic powder core using the mixed soft magnetic powder, and the obtained products and applications. Background Art

[0002] With the rapid development of the electronic information industry, electronic equipment and components are developing towards miniaturization, high frequency, high current and integration, and metal magnetic powder cores are also required to have high magnetic permeability, low loss, high saturation magnetic induction intensity, high DC bias capability, and suitable price. Metal magnetic powder cores mainly include iron powder cores, iron silicon powder cores, sendust powder cores, iron nickel powder cores, iron nickel molybdenum powder cores, and amorphous nanocrystalline powder cores.

[0003] At present, metal magnetic powder cores have problems such as large loss, low saturation magnetic induction intensity, low DC bias, and high price, which cannot meet the development needs. The main manifestations are: the price of iron powder core is low, but the high-frequency characteristics and loss characteristics are poor; the price of iron silicon powder core is moderate, and the DC superposition performance is excellent, but the loss is high, especially the high-frequency loss is high; the iron silicon aluminum powder core has low loss and high cost performance, but the saturation magnetic induction intensity is low and the DC superposition characteristics are not ideal; the iron nickel powder core has the best DC bias characteristics, and the iron nickel molybdenum powder core has the best comprehensive performance, but contains precious metals Ni and Co, and the price is relatively high; the amorphous nanocrystalline powder has high hardness and does not deform during the pressing process, resulting in low density and high porosity of the amorphous nanocrystalline powder core, resulting in low magnetic permeability of the powder core (μ<26), which is not suitable for use. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the above technical background and provide a mixed soft magnetic powder and a method for preparing a soft magnetic powder core using the mixed soft magnetic powder, and the obtained products and applications.

[0005] The invention provides a mixed soft magnetic powder, which comprises A powder, B powder and C powder, wherein: A powder and B powder are independently at least one of iron-based amorphous alloy powder, iron-based nanocrystalline alloy powder and iron-based amorphous nanocrystalline alloy powder, C powder is iron-based alloy powder, and the particle size of A powder is greater than the particle size of C powder and greater than the particle size of B powder.

[0006] In some embodiments of the present invention, A powder, B powder and C powder are obtained by screening the original powder prepared by gas atomization, water atomization or water-gas combined atomization, wherein: the particle size of A powder is -100 mesh to +200 mesh, the particle size of B powder is less than 600 mesh, and the particle size of C powder is -270 mesh to +400 mesh.

[0007] In some embodiments of the present invention, in the mixed soft magnetic powder, the content of A powder is 5wt% to 40wt%, the content of B powder is 15wt% to 50wt%, and the content of C powder is 15wt% to 60wt%.

[0008] In some embodiments of the present invention, A powder or B powder includes at least one of FeSiB, FeSiBC, FeSiBCCr, FeSiBP, FeSiBPC, and FeSiBPCu, and C powder includes at least one of Fe~40%Ni, Fe~50%Ni, and Fe~81%Ni~2%Mo.

[0009] The present invention also provides a method for preparing a soft magnetic powder core using the mixed soft magnetic powder, which comprises: annealing the mixed soft magnetic powder, then performing passivation insulation and coating granulation, and then performing hot pressing and low-temperature annealing to obtain a soft magnetic powder core product.

[0010] In some embodiments of the present invention, after the mixed soft magnetic powder is annealed, passivation insulation and coating granulation include: after the mixed soft magnetic powder is annealed in a hydrogen atmosphere, it is placed in a passivation solution for passivation insulation, and after drying, it is coated and granulated with an organic silicone resin solution to obtain coated powder;

[0011] Preferably, the annealing temperature is 350°C to 500°C, and the time is 0.5h to 5h;

[0012] Preferably, the passivation solution used for passivation insulation is a mixture of phosphoric acid and nitric acid, the phosphoric acid accounts for 40wt% to 80wt%, the water bath temperature is 50°C to 85°C, the stirring time is 15min to 20min, the stirring speed is 100r / min to 500r / min, and after the stirring is completed, the excess acid is removed with alcohol and dried;

[0013] Preferably, the particle size of the material after coating and granulation is controlled between 40 mesh and 150 mesh.

[0014] In some embodiments of the present invention, the temperature of the hot pressing molding is 430°C to 530°C, and the pressure is 16t / cm 2 ~22t / cm 2 .

[0015] In some embodiments of the present invention, the low temperature annealing temperature is 350° C. to 550° C., and the holding time is 0.5 h to 2 h.

[0016] The present invention also provides a soft magnetic powder core prepared according to the above preparation method, the magnetic permeability μ of the soft magnetic powder core is ≥125, and the loss P cv ≤150mW / cm 3 , DC bias characteristics ≥ 76%.

[0017] The present invention also provides an application of the soft magnetic powder core or the soft magnetic powder core prepared according to the method in preparing electronic equipment.

[0018] The present invention has the following beneficial effects.

[0019] The present invention provides a mixed soft magnetic powder and a method for preparing a soft magnetic powder core using the mixed soft magnetic powder, and the obtained product and application. The mixed soft magnetic powder provided by the present invention comprises three kinds of powders, namely A powder, B powder and C powder, of different types and particle sizes. The density of the graded mixed soft magnetic powder is the largest, and the mixed soft magnetic powder filled per unit volume can be the densest, which is conducive to preparing a soft magnetic powder core with high density, high magnetic permeability and low magnetic loss. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0021] Figure 1 The present invention is a flow chart of preparing a soft magnetic powder core using mixed soft magnetic powder. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0023] The following specifically describes a mixed soft magnetic powder provided in an embodiment of the present invention, a method for preparing a soft magnetic powder core using the mixed soft magnetic powder, and the obtained products and applications.

[0024] In the first aspect, an embodiment of the present invention provides a mixed soft magnetic powder, which includes A powder, B powder and C powder, wherein: A powder and B powder are independently at least one of iron-based amorphous alloy powder, iron-based nanocrystalline alloy powder and iron-based amorphous nanocrystalline alloy powder, C powder is an iron-based alloy powder, and the particle size of A powder is greater than the particle size of C powder and the particle size of B powder.

[0025] The embodiment of the present invention provides a mixed soft magnetic powder, including A powder, B powder and C powder. A powder and B powder are amorphous and nanocrystalline alloys derived from amorphous, and can be one or more of amorphous alloy powder, nanocrystalline alloy powder and amorphous nanocrystalline alloy powder. C powder is a soft magnetic alloy powder with a crystalline structure. Although C powder has a high saturation magnetic induction intensity (Bs), its loss (P cv) is high and difficult to use alone, while A powder and B powder have low loss but low saturation magnetic induction intensity. Therefore, the present invention creatively uses C powder with high saturation magnetic induction intensity and A powder and B powder with low loss and low coercivity to compound, which combines the advantages of A powder, B powder and C powder and makes up for the shortcomings of using each alone, that is, the mixed soft magnetic powder has high Bs and low loss. At the same time, the particle size of A powder>the particle size of C powder>the particle size of B powder. Grading the three powders with different particle sizes can further improve the density of the mixed soft magnetic powder, which is conducive to using the above-mentioned mixed soft magnetic powder to prepare a soft magnetic powder core with high density, high magnetic permeability and low magnetic loss.

[0026] In some optional embodiments, A powder, B powder and C powder are obtained by sieving the original powder prepared by gas atomization, water atomization or water-gas combined atomization, wherein: the particle size of A powder is -100 mesh to +200 mesh, the particle size of B powder is below 600 mesh, and the particle size of C powder is -270 mesh to +400 mesh. The above-mentioned A powder is a powder passing through -100 mesh to +200 mesh, B powder is a powder passing through -600 mesh, and C powder is a powder passing through -270 mesh to +400 mesh.

[0027] In some optional embodiments, in the mixed soft magnetic powder, the content of A powder is 5wt% to 40wt%, the content of B powder is 15wt% to 50wt%, and the content of C powder is 15wt% to 60wt%. Optionally, in the mixed soft magnetic powder, the content of A powder is 5wt%, the content of B powder is 35wt%, and the content of C powder is 60wt%; the content of A powder is 10wt%, the content of B powder is 40wt%, and the content of C powder is 50wt%; the content of A powder is 20wt%, the content of B powder is 30wt%, and the content of C powder is 50wt%; the content of A powder is 40wt%, the content of B powder is 40wt%, and the content of C powder is 20wt%, etc.

[0028] In some optional embodiments, A powder or B powder includes at least one of FeSiB, FeSiBC, FeSiBCCr, FeSiBP, FeSiBPC, and FeSiBPCu, and C powder includes at least one of Fe~40%Ni, Fe~50%Ni, and Fe~81%Ni~2%Mo.

[0029] In some optional embodiments, the mixed soft magnetic powder includes the following components in mass percentage:

[0030] -100 mesh ~ +200 mesh A powder 5wt% ~ 40wt%;

[0031] B powder below 600 mesh: 15wt% to 50wt%;

[0032] -270 mesh ~ +400 mesh C powder 15wt% ~ 60wt%.

[0033] An embodiment of the present invention provides a mixed soft magnetic powder, including A powder, B powder and C powder. The powder raw materials are scientifically proportioned and optimized based on their particle size, proportion and type. The particles in the maximum particle size range are used as the benchmark, the particles in the secondary particle size range are filled in the gaps between the particles in the maximum particle size range, and the particles in the small particle size range are filled in the particles in the larger particle size range. The density of the obtained mixed soft magnetic powder is the largest, which is conducive to using the above-mentioned mixed soft magnetic powder to prepare a soft magnetic powder core with high density, high magnetic permeability and low magnetic loss.

[0034] In a second aspect, an embodiment of the present invention further provides a method for preparing a soft magnetic powder core using the above-mentioned mixed soft magnetic powder, see Figure 1 , including the following steps:

[0035] Step S100: selecting amorphous raw powder (or nanocrystalline raw powder) and iron-based alloy raw powder prepared by vacuum air atomization or water atomization, sieving the raw powders to obtain three powders with different particle sizes, namely, powder A, powder B and powder C, and mixing the three powders with different particle sizes evenly to obtain mixed soft magnetic powder;

[0036] Step S200: annealing the mixed soft magnetic powder under hydrogen protection, and sequentially passivating and insulating and coating and granulating the annealed powder to obtain coated powder;

[0037] Step S300: pressing the coated powder into a soft magnetic powder core green body;

[0038] Step S400: subjecting the magnetic powder core green body to low temperature annealing to obtain a soft magnetic powder core finished product.

[0039] In some optional embodiments, in step S200, the temperature of the mixed soft magnetic powder annealing treatment is 350°C to 500°C, and the time is 0.5h to 5h. Annealing the mixed soft magnetic powder in a hydrogen atmosphere can reduce the impurity content and lattice defects in the powder, and can reduce the internal stress and coercive force generated in the powder preparation process. Optionally, the annealing temperature can be 350°C, 400°C, 450°C, 500°C and any other value between 350 and 500°C, and the annealing time can be 0.5h, 1.0h, 2.0h, 3.0h, 4.0h, 5.0h and any other value between 0.5h and 5h.

[0040] In some optional embodiments, in step S200, the passivation solution used for passivation insulation is a mixture of phosphoric acid and nitric acid, the phosphoric acid accounts for 40wt% to 80wt%, the water bath temperature is 50℃ to 85℃, the stirring time is 15min to 20min, the stirring speed is 100r / min to 500r / min, and after the stirring is completed, the excess acid is removed with alcohol and dried. In the process of passivation insulation, high-speed stirring can improve sphericity, reduce irregular powder, and improve the coating effect. Optionally, the proportion of phosphoric acid in the passivation solution can be 40wt%, 50wt%, 60wt%, 70wt%, 80wt% and any other value between 40wt% and 80wt%, the water bath temperature can be 50°C, 60°C, 70°C, 80°C and any other value between 50°C and 85°C, the stirring time can be 15min, 17min, 18min, 20min and any other value between 15min and 20min, and the stirring speed can be 100r / min, 200r / min, 300r / min, 400r / min, 500r / min and any other value between 100r / min and 500r / min.

[0041] In some optional embodiments, in step S200, the particle size of the coated powder after coating and granulation is controlled between 40 and 150 meshes. After passivation and insulation, coating and granulation are performed to firmly wrap the inner inorganic coating layer by utilizing the viscosity of the organic coating layer, effectively preventing the inorganic coating layer from breaking and falling off during the pressing process.

[0042] In some optional embodiments, in step S300, the temperature of the hot pressing molding is 430°C to 530°C, and the pressure is 16t / cm 2 ~22t / cm 2 . Compared with the cold pressing process, hot pressing can reduce the stress during the pressing process. In addition, since the hardness of the amorphous powder and nanocrystalline powder (such as A powder and B powder) in the mixed soft magnetic powder is relatively high, and the hardness of the iron-based alloy powder (such as C powder) is relatively low, the iron-based alloy powder is deformed during the hot pressing process and can fill the gaps between the mixed soft magnetic powders to reduce the porosity. The amorphous powder and nanocrystalline powder have plasticity when they are in the supercooled liquid phase, which can further increase the density of the magnetic powder core. Optionally, the temperature of hot pressing can be 430°C, 450°C, 470°C, 490°C, 510°C, 530°C and any other value between 430°C and 530°C, and the pressure can be 16t / cm 2 、18t / cm 2 , 20t / cm 2 , 22t / cm 2 and 16t / cm 2 ~22t / cm 2 Any other value in between.

[0043] In some optional embodiments, the temperature of low temperature annealing is 350°C to 550°C, and the holding time is 0.5h to 2h. The low temperature annealing treatment method is adopted to further eliminate the residual stress in the powder core while reducing energy consumption, and effectively improve the performance and service life of the soft magnetic powder core. Optionally, the temperature of low temperature annealing can be 350°C, 400°C, 450°C, 500°C, 550°C and any other value between 350°C and 550°C, and the holding time can be 0.5h, 1h, 1.5h, 2h and any other value between 0.5h and 2h.

[0044] In a third aspect, an embodiment of the present invention further provides a soft magnetic powder core prepared according to the above method, wherein the magnetic permeability μ of the soft magnetic powder core is ≥ 125, and the loss P cv ≤150mW / cm 3 , DC bias characteristics ≥ 76%.

[0045] In a fourth aspect, an embodiment of the present invention further provides a use of the soft magnetic powder core or the soft magnetic powder core prepared according to the above method in preparing electronic equipment.

[0046] The present invention will be further described below in conjunction with the embodiments.

[0047] A method for preparing mixed soft magnetic powder, see Figure 1 , including the following steps:

[0048] Step S100: Select the raw powder prepared by the vacuum air atomization method, sieve the raw powder separately to obtain three kinds of powders, namely, A powder of -100 mesh to +200 mesh, B powder below 600 mesh, and C powder of -270 mesh to +400 mesh, mix the above three kinds of powders to obtain a mixed soft magnetic powder, wherein: A powder and B powder are independently at least one of iron-based amorphous alloy powder, iron-based nanocrystalline alloy powder and iron-based amorphous nanocrystalline alloy powder, C powder is iron-based alloy powder, and A powder accounts for 5wt% to 40wt%, B powder accounts for 15wt% to 50wt%, and C powder accounts for 15wt% to 60wt%.

[0049] Step S200: annealing the mixed soft magnetic powder obtained above in a hydrogen atmosphere, the annealing temperature is 350℃~500℃, and the annealing time is 0.5h~5h; placing the annealed mixed soft magnetic powder into a water bath stirring pot for passivation insulation treatment, the passivation solution used is a mixture of phosphoric acid and nitric acid (the phosphoric acid ratio is 40wt%~80wt%), the water bath temperature is 50℃~85℃, the stirring time is 15min~20min, and the stirring speed is 100r / min~500r / min; after stirring, remove excess acid with alcohol, dry, and then coat and granulate and control the particle size between 40 mesh and 150 mesh to obtain coated powder.

[0050] Step S300: The coated powder obtained above is formed into a soft magnetic powder core green body by hot pressing molding process, the hot pressing temperature is 430℃~530℃, the pressure is 16t / cm 2 ~22t / cm 2 .

[0051] Step S400: placing the obtained soft magnetic powder core green body into a vacuum furnace for low temperature annealing, controlling the low temperature annealing temperature to be 350° C. to 550° C., keeping the temperature for 0.5 h to 2 h, and naturally cooling to room temperature to obtain a soft magnetic powder core finished product.

[0052] The following Table 1 shows the types, particle sizes and contents of the powders used in the examples and comparative examples, Table 2 shows the process parameters in the examples and comparative examples, and Table 3 shows the test results.

[0053] Table 1

[0054]

[0055] Table 2

[0056] serial number Hydrogen annealing temperature℃ Hot pressing temperature℃ <![CDATA[Pressure t / cm 2 > Low temperature annealing temperature℃ Insulation time Require 350~500 430~530 16~22 350~550 0.5~2 Example 1 465 495 21 480 1 Example 2 460 495 21 480 1h Example 3 450 495 21 480 1h Example 4 465 495 21 480 1h Comparative Example 1 600 550 21 480 1h Comparative Example 2 465 550 21 480 1h Comparative Example 3 465 495 21 480 1h Comparative Example 4 300 425 21 600 1h Comparative Example 5 465 495 21 480 1 Comparative Example 6 465 495 21 480 1 Comparative Example 7 465 495 21 480 1

[0057] Table 3

[0058] serial number Magnetic permeability, μ Power consumption, 50KHz / 100mT DC superposition characteristics%, DC~Bias(100Oe) Require >125 <150 >76 Example 1 158 116 81 Example 2 155 130 83 Example 3 148 128 80 Example 4 152 112 79 Comparative Example 1 153 561 78 Comparative Example 2 130 460 82 Comparative Example 3 118 106 77 Comparative Example 4 124 483 81 Comparative Example 5 146 286 75 Comparative Example 6 96 126 83 Comparative Example 7 108 142 79

[0059] It can be seen from Tables 2 and 3 above that: as the proportion of A powder in the mixed soft magnetic powder decreases, the magnetic permeability of the soft magnetic powder core decreases; as the proportion of B powder increases, the DC superposition of the soft magnetic powder core increases; as the proportion of C powder increases, the loss of the soft magnetic powder core decreases; when the annealing temperature or the pressing temperature exceeds 550°C, the amorphous powder changes from an amorphous state to a crystalline state, and the loss of the soft magnetic powder core increases significantly. It can be seen that the present invention prepares a soft magnetic powder core with high density, high magnetic permeability, low loss and good DC bias capability through the scientific ratio of raw materials (grading raw material powders of different particle sizes, proportions and types) and the optimized design of the preparation process. The soft magnetic powder core has excellent comprehensive performance and broad market prospects.

[0060] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A mixed soft magnetic powder, characterized in that: The mixed soft magnetic powder includes A powder, B powder and C powder, wherein: the A powder and the B powder are independently at least one of iron-based amorphous alloy powder, iron-based nanocrystalline alloy powder and iron-based amorphous nanocrystalline alloy powder, the C powder is an iron-based alloy powder, and the particle size of the A powder is greater than the particle size of the C powder and the particle size of the B powder.

2. The mixed soft magnetic powder according to claim 1, characterized in that: The A powder, the B powder and the C powder are obtained by screening the original powders prepared by gas atomization, water atomization or water-gas combined atomization, wherein: the particle size of the A powder is -100 mesh to +200 mesh, the particle size of the B powder is below 600 mesh, and the particle size of the C powder is -270 mesh to +400 mesh.

3. The mixed soft magnetic powder according to claim 1, characterized in that: In the mixed soft magnetic powder, the content of the A powder is 5wt% to 40wt%, the content of the B powder is 15wt% to 50wt%, and the content of the C powder is 15wt% to 60wt%.

4. The mixed soft magnetic powder according to claim 1, characterized in that: The A powder or the B powder includes at least one of FeSiB, FeSiBC, FeSiBCCr, FeSiBP, FeSiBPC, and FeSiBPCu, and the C powder includes at least one of Fe~40%Ni, Fe~50%Ni, Fe~81%Ni~2%Mo.

5. A method for preparing a soft magnetic powder core using the mixed soft magnetic powder according to any one of claims 1 to 4, characterized in that: It includes: The mixed soft magnetic powder is annealed, then passivated and insulated, coated and granulated, and then hot pressed and low-temperature annealed to obtain a soft magnetic powder core product.

6. The method according to claim 5, characterized in that After the mixed soft magnetic powder is annealed, passivation insulation and coating granulation are performed, which includes: annealing the mixed soft magnetic powder in a hydrogen atmosphere, placing the mixed soft magnetic powder in a passivation solution for passivation insulation, drying the mixed soft magnetic powder, and then coating granulation with an organic silicone resin solution to obtain coated powder; Preferably, the annealing temperature is 350°C-500°C and the time is 0.5h-5h; Preferably, the passivation solution used for passivation insulation is a mixture of phosphoric acid and nitric acid, the phosphoric acid accounts for 40wt%-80wt%, the water bath temperature is 50℃-85℃, the stirring time is 15min-20min, the stirring speed is 100r / min-500r / min, and after the stirring is completed, the excess acid is removed with alcohol and dried; Preferably, the particle size of the material after coating and granulation is controlled between 40 mesh and 150 mesh.

7. The method according to claim 5, characterized in that The temperature of the hot pressing molding is 430℃-530℃ and the pressure is 16t / cm 2 -22t / cm 2 .

8. The method according to claim 5, characterized in that The low-temperature annealing temperature is 350° C.-550° C., and the holding time is 0.5 h-2 h.

9. A soft magnetic powder core prepared by the method according to any one of claims 5 to 8, characterized in that: The magnetic permeability μ of the soft magnetic powder core is ≥125, and the loss P cv ≤150mW / cm 3 , DC bias characteristics ≥ 76%.

10. Use of the soft magnetic powder core prepared by the method according to any one of claims 5 to 8 or the soft magnetic powder core according to claim 9 in preparing electronic equipment.

Citation Information

Cited By

  • Composite magnetic material, preparation method thereof and magnetic device

    CN121528672A